Study Of Medication Utilization Evaluation in Patients with Chronic Kidney Disease and Acute Renal Disease in Tertiary Care Hospital: An Cross- Sectional Study - B. Jankar, Bhausaheb; J. Patil, Ramanand; K. Choure, Balwant; Sawant, Sushant (Journal of Neonatal Surgery, 2025)
Background: Medication utilization evaluation involves the assessment of drug marketing, distribution, prescribing, and usage within a society, with particular focus on the associated medical, social, and economic outcomes. DUE is a continuous, authorized, and systematic process aimed at improving the quality of healthcare. AKI and CKD are interrelated syndromes, with AKD (7–90 days post-AKI) serving as a critical phase for intervention to prevent CKD progression. AKD is associated with high morbidity, especially in elderly and comorbid patients. Globally, AKI impacts 13.3 million people annually, with 1.7 million deaths. Management includes recurrence prevention, early nephrology referral, and targeted therapies such as RAS inhibitors. This study evaluates medication utilization patterns in chronic kidney disease using WHO core drug use indicators to identify and improve rational prescribing practices. Methodology: Approval from the Institutional Ethics Committee, a descriptive cross-sectional study was conducted over a one-year period (March 2023 to February 2024) to evaluate the prescription patterns and drug utilization in patients with renal diseases. The study was carried out in the Nephrology Outpatient Department of a tertiary care hospital in Sangli, Maharashtra, India. Results: In this study of 200 renal patients, CKD was more prevalent (79%) than AKI. The mean drugs per prescription were 6.5 ± 2.2, with 64% prescribed by brand name and 76% from the NLEM. Tablets were the most common dosage form (70%), and erythropoietin and nifedipine were the most frequently used supplement and antihypertensive, respectively. Conclusions: This study highlights that CKD was the predominant diagnosis among renal patients, with frequent polypharmacy and high use of essential medicines. The findings underscore the need for rational prescribing practices and increased use of generics to optimize outcomes and reduce treatment costs.